Efeitos do treinamento multicomponente sobre aspectos hemodinâmicos e funcionais de mulheres idosas - Souza, Tállita Cristina Ferreira de (2020)
The present study aimed to analyze the hemodynamic and physical ability effects after two different models of multicomponent training in elderly women. 41 elderly women, aged between 60 and 80 years, who were assigned to two types of intervention (MT1 or MT2) and control group (CON) participated. MT1 performed a mixed-functional exercise routine involving strength, aerobic, balance, agility, coordination and flexibility in the same session, while MT2 used the same physical capacities, however, in divided sessions, characterized as a uni-functional routine, both with three weekly training sessions for 12 weeks. For evaluation, anthropometric (characterization), cardiovascular and physical ability measurements were performed. The statistical analysis was processed using the generalized estimation equation (GEE) with Bonferroni's post hoc (ɑ = 0.05). In physical ability, there was significant interaction (time * group) in all variables, and both MT1 and MT2 improved the strength of lower limbs (MT1 = 15.22% and MT2 = 31.35%) and upper (MT1 = 28, 39% and MT2 = 24.26%), coordination (MT1 = 16.25% and MT2 = 40.62%), agility and dynamic balance (MT1 = 4.68% and MT2 = 14.85%) , flexibility (MT1 = 10.83% and MT2 = 15.76%) and aerobic resistance (MT1 = 5.98% and MT2 = 5.18%) after training. In the analysis of heart rate variability, RR intervals (MT1 = 9.25%, MT2 = 2.09% and CON = 12.99%), SDNN indices (MT1 = 1.66%, MT2 = 34.25 % and CON = 14.57%), RMSSD (MT1 = 5.44%, MT2 = 3.84% and CON = 22.79%) and heart rate (MT1 = 9.34%, MT2 = 1.01 % and CON = 13.87%) improved significantly as a function of time in all groups. There were no significant differences in any of the hemodynamic variables (SBP, DBP, MBP, PP and DP). Our study showed that mixed and single-functional TMs were able to improve physical capacities in the variables of strength, coordination, agility and dynamic balance, flexibility and aerobic endurance, as well as HRV and maintain BP values without medication adjustment, after training with elderly women.